Iron Oxide‐Labeled Collagen Scaffolds for Non‐Invasive MR Imaging in Tissue Engineering. (28th August 2013) - Mertens, Marianne E.; Hermann, Alina; Bühren, Anne; Olde‐Damink, Leon; Möckel, Diana; Gremse, Felix; Ehling, Josef; Kiessling, Fabian; Lammers, Twan
<x xml:space="preserve">Abstract</x> Non‐invasive imaging holds significant potential for implementation in tissue engineering. It can be used to monitor the localization and function of tissue‐engineered implants, as well as their resorption and remodelling. Thus far, however, the vast majority of effort in this area of research have focused on the use of ultrasmall super‐paramagnetic iron oxide (USPIO) nanoparticle‐labeled cells, colonizing the scaffolds, to indirectly image the implant material. Reasoning that directly labeling scaffold materials might be more beneficial (enabling imaging also in the case of non‐cellularized implants), more informative (enabling the non‐invasive visualization and quantification of scaffold degradation), and easier to translate into the clinic (cell‐free materials are less complex from a regulatory point‐of‐view), three different types of USPIO nanoparticles are prepared and incorporated both passively and actively (via chemical conjugation; during collagen crosslinking) into collagen‐based scaffold materials. The amount of USPIO incorporated into the scaffolds is optimized, and correlated with MR signal intensity, showing that the labeled scaffolds are highly biocompatible, and that scaffold degradation can be visualized using MRI. This provides an initial proof‐of‐principle for the in vivo visualization of the scaffolds. Consequently, USPIO‐labeled scaffold materials seem to be highly suitable for image‐guided tissue engineering applications.